MIDDLE TO LATE JURASSIC BIOFACIES OF SAUDI ARABIA - GERAINT W. HUGHES (Rivista Italiana di Paleontologia e Stratigrafia, 2004)
Saudi Arabian Jurassic carbonate hydrocarbon reservoirs were first examined stratigraphically using microfauna. Current microfaunal studies concentrate on the identification and constraint of palaeoenvironmental variations and determination of high-resolution depositional cyclicity of the reservoir carbonates. It is apparent that the environmental sensitivity of benthonic foraminifera provides a potentially valuable technique for the determining subtle variations in the depositional environment and also providing a proxy for sea-level fluctuations.